Catalytic behavior of graphene oxide for cement hydration process. (February 2016) - Lin, Changqing; Wei, Wei; Hu, Yun Hang
Abstract: Hydration is a critical step that determines the performance of cement-based materials. In this paper, the effect of GO on the hydration of cement was evaluated by XRD and FTIR. It was found that GO can remarkably accelerate the hydration rate of cement due to its catalytic behavior. This happened because the oxygen-containing functional groups of GO provide adsorption sites for both water molecules and cement components. Highlights: GO can remarkably accelerate the hydration of cement. GO can play a catalytic role in cement hydration. Water molecules on GO constitute a water reservoir and water transport channels.